Measures of problem gambling, gambling behaviours and perceptions of gambling in Ireland - Diarmaid Ó Ceallaigh; Shane Timmons; Deirdre Robertson; Pete Lunn (The Economic and Social Research Institute (ESRI), 2023)
Problem gambling (PG) describes gambling behaviour that is disruptive or damaging to individuals, and includes behaviours (e.g., betting more than one can afford to lose) and experiences (e.g., feeling guilt and anxiety about gambling). This study set out to measure the prevalence of PG in Ireland. Previous measures of PG have been undertaken using in-person surveys, but international evidence suggests that gambling is a sensitive behaviour and that people may be reluctant to reveal honestly how much they gamble to an interviewer. For the present study, participants completed the questionnaire online to facilitate greater anonymity and promote more honest responding to sensitive questions. The study was undertaken in August 2023 by quota sampling, using three different online panels, which generated a total usable sample of 2,850 adults aged 18 and over. The use of online panels and the sampling method more generally means the results may not generalise to people without internet access, those who are over 80 years of age or individuals without the capacity to complete surveys in English (e.g., those with cognitive impairments, some minority groups). To improve representativeness outside of these characteristics, we reweighted responses by age, gender and educational attainment based on Census 2022 figures. The main aim of the study is to measure the prevalence of PG but secondary aims include providing measures of gambling activity and perceptions of gambling among the general population. The focus of the report is on describing and measuring the problem; detailed causal analyses will feature in future reports.
Keywords: 330